Evaluasi Praklinis Asam Askorbat pada Sepsis Eksperimental dan Kesenjangan Penelitian Centella asiatica pada Sepsis Terinduksi Staphylococcus aureus: Tinjauan Literatur Sistematis - Sabar Hamonangan Victorianus Napitu; Gusbakti Rusip; Maya Sari Mutia; Yolanda Eliza Putri Lubis (Journal of Pharmaceutical and Sciences, 2026)
Background: Adjunctive antioxidant therapy has been extensively investigated in experimental sepsis; however, evidence regarding the combined effects of Centella asiatica extract and ascorbic acid on survival outcomes remains limited. This systematic review aimed to evaluate preclinical evidence on the survival benefits of C. asiatica extract and/or ascorbic acid in experimental sepsis, particularly in Staphylococcus aureus-induced models, and to identify research gaps. Methods: A systematic review was conducted following PRISMA guidelines. Comprehensive literature searches were performed in Scopus (n=126) and Google Scholar (n=467) to identify controlled in vivo rat studies evaluating C. asiatica extract and/or ascorbic acid supplementation in sepsis models with reported survival outcomes. Data extraction covered intervention characteristics, sepsis models, survival endpoints, inflammatory markers, oxidative stress parameters, organ injury indicators, and statistical analyses. Results: Of 593 initial records, 403 were screened after duplicate removal, and five studies met eligibility criteria. All included studies evaluated ascorbic acid monotherapy in sepsis models induced by lipopolysaccharide (LPS), cecal ligation and puncture (CLP), or fecal intraperitoneal injection (FIP); none used S. aureus and none evaluated C. asiatica extract. Ascorbic acid monotherapy consistently improved survival: 48-hour survival increased from 5.5% to 61% (p<0.0007) and 7-day survival from 30% to 45% (p<0.05) in CLP models, accompanied by reduced pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, CRP), decreased oxidative stress, and attenuated multiorgan injury. Conclusion: This review identifies a critical research gap: no preclinical study has evaluated C. asiatica extract, alone or in combination with ascorbic acid, in S. aureus-induced sepsis. The available evidence is limited to ascorbic acid monotherapy in alternative sepsis models, which cannot be directly generalized to staphylococcal sepsis due to pathophysiological differences. Direct experimental studies using validated S. aureus sepsis models are urgently needed before any therapeutic recommendation can be made.